Meningkatkan Pemahaman Peserta Didik Terhadap Materi Ekosistem Melalui Model Discovery Learning - ., Ani Anjarwati; ., Ika Putri Fadilah; ., Adenita Faradilla; ., Devi Puspita; ., Uul Zahro Aulia (CV. ITTC INDONESIA, 2022)
The development of HOTS (Higher Out Thinking Skills) based questions is very important to be developed in elementary schools to assist students in developing higher order thinking skills. This study aims to develop test questions proposed by Bloom's taxonomy, namely from C4 (analyze), C5 (evaluate), and C6 (create). Based on the results of PTK or classroom action research at SDN Sukabumi 2, Probolinggo City, it was found that the Discovery Learning method made fifth grade students understand what was conveyed by the author about natural science subjects on ecosystems through power point learning media and learning videos. So the writer wants to test the ability of fifth grade students by giving Pre-Test and Post-Test questions. From the pre-test questions based on the cognitive domain at the LOTS level, students managed to get the highest score, namely 90 in the